Physicians' challenges under El Salvador's criminal abortion prohibition. Issue 1 (30th July 2018) - Zureick, Alyson; Khan, Amber; Chen, Angeline; Reyes, Astrid
Abstract: El Salvador's criminal abortion law—one of the few in the world that prohibits all abortions and that is actively enforced against women—harms women's health and undermines the ethical duties of Salvadoran physicians and the standing of the medical profession. Under the criminal abortion regime, physicians are incentivized to disclose their patients' confidential medical information, in violation of their ethical duties, and public healthcare facilities have become sites of criminal investigation. These investigations target women not only for illegal abortions, but also for miscarriages and obstetric emergencies. The ban further prevents physicians from providing medical care that is often necessary to preserve a woman's life or health. Finally, by criminalizing women's pregnancy outcomes, the regime undermines the country's recent public health improvement efforts and compounds the marginalization of women and girls from its most vulnerable communities, in violation of the state's international human rights obligations. Abstract : El Salvador's criminal abortion ban undermines the medical profession's ethical duties and standing, and the health and human rights of marginalized women and girls.